Peer Feedback to Improve Indonesian Adult Learners’ Writing Skills: A Review - Damanik, Juli Yanti (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
Demonstrating good writing skills in English is considered important to master for students in tertiary level. In addition, as higher education institutions in Indonesia have been conducting teaching and learning activities online to mitigate Covid-19 viral spread, students’ engagement in learning has been reported to be low due to boredom and tiresome in an online learning environment. Therefore, teachers need to plan and implement strategies to promote students’ skills in writing and students’ engagement in learning activities, in this case writing course. One of them is by practicing peer feedback. The purpose of this paper is to critically review peer feedback in improving Indonesian adult learners’ writing skills in English course. In this literature review, 23 documents (a book chapter and peer-reviewed articles) were synthesized to find how peer feedback is relevant and beneficial in the tertiary education context. This paper argues that peer feedback is advantageous in improving adult learners’ writing skills in that it facilitates meaning negotiation, it fosters critical thinking, and it promotes collaborative learning. However, teachers should anticipate possible issues emerging in peer feedback practice by providing pre-requisite training for students.